Correlation between serum zinc levels and successful immunotherapy in recurrent spontaneous abortion patients - Ahad Zare; Abotaleb Saremi; Marjan Hajhashemi; Gholam Ali Kardar; Seyed Mohammad Moazzeni; Zahra Pourpak; Pirouz Salehian; Maryam Naderi; Reza Safaralizadeh; Maryam Nourizadeh (Wolters Kluwer Medknow Publications, 2013)
Background: Immunotherapy with paternal lymphocytes plays an important role in preventing recurrent spontaneous abortion (RSA) and is an effective treatment for it. This kind of treatment is performed as an immunotherapy method in several centers in the world. It attributes to the production of anti-paternal cytotoxic antibodies (APCAs) in women with RSA. Production of APCA after lymphocyte immunotherapy (LIT) in RSA patients gives them a better chance for successful pregnancy. Regarding the important effect of trace elements on the function of the immune system, we tried to investigate the correlation between serum zinc level and the success of LIT in RSA. Materials and Methods: Serum zinc concentration was determined in two groups of RSA patients using atomic absorption spectrophotometer systems. Group (a) that responded to the paternal lymphocytes and their cross-match test was positive, and group (b) that had no response to the paternal lymphocytes immunizations and their cross-match test was negative. Results: Serum zinc levels in group (a) patients were 74.98 ± 11.88 μg/dl, which was significantly higher than those in group (b) with the zinc concentration of 64.22 ± 9.22 μg/dl. Conclusions: Zinc deficiency may be one of the substantial causes of negative results for LIT in RSA patients. Therefore, compensation of zinc defect before LIT can be a promising approach to improve the immune response in patients.